Innovation and Job Creation: A sustainable relation? - Daria Ciriaci; Pietro Moncada-Paternò-Castello; Peter Voigt (European Commission, Joint Research Centre (JRC), 2013)
This study examines growth patterns of innovative and non innovative firms and, in this regard, whether being an innovator determines company trajectories; i.e. whether there are systematic differences in the persistence of the jobs created by innovating vs. non-innovating firms. For this purpose, a semi-parametric quantile regression approach has been adopted examining serial correlation in employment by drawing on a unique longitudinal dataset of 3,300 Spanish firms over the years 2002-2009, obtained by matching different waves of the Spanish Encuesta sobre Innovacion en las Empresas, the Spanish innovation survey, which is administered every year by the Spanish National Statistics Institute (INE). The empirical results of the study indicate that among those firms experiencing high organic employment growth, smaller and younger innovative firms grow more, at average, than larger innovative firms. Moreover, the jobs created by innovative firms, in general, appear to be rather persistent over time whereas those created by non innovative firms do not. Among declining firms, non-innovators tend to deteriorate faster in terms of economic performance. Overall, evidence suggests that being innovative supports and stabilizes a firm's organic employment growth pattern and being smaller and younger seems to be a sufficient condition to experience high employment growth, i.e. – with regard to the latter – it is not necessary to have a comparably high R&D spending / being an R&D intensive company.
Keywords: L11; L25; 330; Serial correlation; quantile regression; Spanish firms; firm size; firms age; job creation; YICs